2007
DOI: 10.1002/nau.20389
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between the ICIQ‐SF score and urodynamic findings

Abstract: ICIQ-SF scoring is a practical and reliable method for baseline and post-treatment evaluation of patients with urge incontinence. Significant correlation exists between ICIQ-SF score and urodynamic parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0
9

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(35 citation statements)
references
References 10 publications
1
25
0
9
Order By: Relevance
“…In addition, urinary disturbances based on the Incontinence Questionnaire-Urinary Incontinence Short Form and clinical examination such as urinary frequency, incontinence, and feeling of incomplete emptying were evaluated before and after the treatment [30][31][32]. A positive response was mainly considered as an improvement in motor function, urinary symptoms, and neurologic signs.…”
Section: Clinical Evaluationmentioning
confidence: 99%
“…In addition, urinary disturbances based on the Incontinence Questionnaire-Urinary Incontinence Short Form and clinical examination such as urinary frequency, incontinence, and feeling of incomplete emptying were evaluated before and after the treatment [30][31][32]. A positive response was mainly considered as an improvement in motor function, urinary symptoms, and neurologic signs.…”
Section: Clinical Evaluationmentioning
confidence: 99%
“…The present study showed a significant correlation between this questionnaire and urodynamics, and the questionnaire was considered "gold standard" to assess UI. 30 Hajebrahimi et al reported equivalent results when the questionnaire was answered by the subject or completed by the researcher. 31 When it was not possible to administer questionnaires to a family because of the absence of residents or lack of subjects that could be included in the study, an attempt was made with the next registered family (the family related to the next number).…”
Section: Methodsmentioning
confidence: 98%
“…Furthermore, standardised and validated questionnaires were prospectively utilized for the evaluation of quality of life (QoL) and satisfaction rate. The following questionnaires were used: "incontinence -QoL" [8] (I-QoL; scale: 0-100, higher score presents better QoL), "Patient Global Impression of Improvement" (PGI-I) [9] (range 1-7, very much better to very much worse), "international consultation on incontinence questionnaire-short form" (ICIQ-SF) [10,11] (range 0-21, 0 = no incontinence, 1-5 = slight, 6-12 = moderate, 13-18 = severe, 19-21 = very severe), "Verbale Rating Scale of Pain" (range 0-10, minimal to maximum pain) for perineum, genitals, inguinal groin and symphysis. The preoperative evaluation included detailed incontinence history, sonography, cystoscopy, and urodynamics if needed.…”
Section: Methodsmentioning
confidence: 99%